Pendampingan keluarga dalam memodifikasi lingkungan bebas malaria di Desa Mbatakapidu - Njakatara, Umbu Nggiku; Abselian, Umbu Putal; Landi, Melkisedek; Radandima, Ester; Gracela, Gracela; Theresa, Theresa; Arnesta, Arnesta (Penamas: Journal of Community Service, 2025)
The prevalence of malaria in East Sumba Regency reached 2,184 cases in 2023. In 2022, there were 135 cases in the Waingapu Community Health Center's work area, including Mbatakapidu Village. This raises the urgency of immediate action to address partner issues. Waingapu Community Health Center data show that 12 malaria cases were reported in 2020 and 58 in 2021. The main contributor to cases came from Mbatakapidu Village. Therefore, malaria promotion and prevention activities are focused on that village. This community service activity aims to provide assistance and health education to families about mosquito-repellent plants, namely citronella trees. The implementation method involves counselling, introducing, and distributing mosquito-repellent plant seeds. This activity was carried out with a pre-test and post-test, with average scores of 62% and 92%, respectively, resulting in a 30% increase in knowledge. The target output of this community service activity is articles and activity videos that can be published in journals and online mass media.